Does Urbanization Affect Predation of Bird Nests? A Meta-Analysis - Vincze, Ernő; Seress, Gábor; Lagisz, Malgorzata; Nakagawa, Shinichi; Dingemanse, Niels J.; Sprau, Philipp (Frontiers in Ecology and Evolution, 2017)
Urbanization can affect interspecific interactions such as predator-prey relationships. Several hypotheses have been postulated to predict how predation on bird nests changes along urbanization gradients; some predict increased and others decreased predation pressures in urban compared to rural habitats. Using a formal meta-analytical approach, we carried out a systematic literature review to test whether predation on natural and artificial bird nests increased or decreased with urbanization. We found that the effect was highly heterogeneous among studies, due to contrasting results between studies that used artificial nests and those that used natural nests. For artificial nests, survival rate tended to decrease with increasing urbanization, with higher predation in more urbanized study sites. For natural nests, survival tended to increase with the level of urbanization. The latter finding supports predictions of the ‘urban habitats as predation-safe zones’ and ‘urban nest predator paradox’ hypotheses, but the effect may be confounded by many studies not distinguishing between predation and other sources of mortality. None of the other considered methodological and ecological variables explained the variation in a robust way. The discrepancy between the results of artificial and natural nest studies may be due to differences in experimental design (e.g., cavity nests have been more commonly studied in natural nest studies), intrinsic differences between the two nest types (e.g., lack of parental nest defense in artificial nests), or sampling bias. We conclude that the direction of the relationship between urbanization and nest predation is likely to depend on the methodology of the study. Therefore, results from studies using different methodologies, particularly natural or artificial nests, should be generalized with caution to avoid over-interpretations.